2007
DOI: 10.1111/j.1365-2133.2007.08156.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute generalized exanthematous pustulosis (AGEP)—results of a multinational case–control study (EuroSCAR)

Abstract: Medications associated with AGEP differ from those associated with Stevens-Johnson syndrome or toxic epidermal necrolysis. Different timing patterns from drug intake to reaction onset were observed for different drugs. Infections, although possible triggers, played no prominent role in causing AGEP and there was no evidence that AGEP is a variant of pustular psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
432
5
28

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 476 publications
(484 citation statements)
references
References 50 publications
(62 reference statements)
19
432
5
28
Order By: Relevance
“…34 Although the infectious etiology of AGEP is still controversial, 32.36 there are reports of patients with skin lesions compatible with AGEP during an infectious process without use of any medication. 34,35,37 Approximately 90% of the cases are caused by medication. 34.38 Among the drugs commonly associated with the development of AGEP are antibiotics (macrolides and beta-lactams), antifungals, calcium channel blockers, carbamazepine, paracetamol, anti-malarial drugs, among others.…”
Section: Acute Generalized Exanthematous Pustulosismentioning
confidence: 99%
See 4 more Smart Citations
“…34 Although the infectious etiology of AGEP is still controversial, 32.36 there are reports of patients with skin lesions compatible with AGEP during an infectious process without use of any medication. 34,35,37 Approximately 90% of the cases are caused by medication. 34.38 Among the drugs commonly associated with the development of AGEP are antibiotics (macrolides and beta-lactams), antifungals, calcium channel blockers, carbamazepine, paracetamol, anti-malarial drugs, among others.…”
Section: Acute Generalized Exanthematous Pustulosismentioning
confidence: 99%
“…33.36 It is worth noting that the spectrum of agents associated with toxic epidermal necrolysis/Stevens-Jonhson syndrome differs from the medication associated with AGEP. 35 The EuroScar multicentric study showed that some drugs are more likely (higher odds ratio) to lead to the development of AGEP (Table 1). 35 The sensitization phase is not well understood, but it is believed that antigen-presenting cells activate T cells by presenting the drug to the lymph node.…”
Section: Acute Generalized Exanthematous Pustulosismentioning
confidence: 99%
See 3 more Smart Citations